Development of a separable search-and-rescue robot composed of a mobile robot and a snake robot. (17th January 2020) - Kamegawa, Tetsushi; Akiyama, Taichi; Sakai, Satoshi; Fujii, Kento; Une, Kazushi; Ou, Eitou; Matsumura, Yuto; Kishutani, Toru; Nose, Eiji; Yoshizaki, Yusuke; Gofuku, Akio
Abstract: In this study, we propose a new robot system consisting of a mobile robot and a snake robot. The system works not only as a mobile manipulator but also as a multi-agent system by using the snake robot's ability to separate from the mobile robot. Initially, the snake robot is mounted on the mobile robot in the carrying mode. When an operator uses the snake robot as a manipulator, the robot changes to the manipulator mode. The operator can detach the snake robot from the mobile robot and command the snake robot to conduct lateral rolling motions. In this paper, we present the details of our robot and its performance in the World Robot Summit. GRAPHICAL ABSTRACT: